Analisis Sistem Perawatan Boiler di PT. Dewa Rencana Perangin-Angin - Polewangi, Yudi Daeng (Universitas Medan Area, 2018)
Boilers are closed vessels made of steel that use to produce steam and be used for heating, turbine driving and so on. Good maintenance for boiler will make the efficiency of boiler higher and save general operational cost. Boiler condition in PT. Dewa Rencana Perangin-angin experiences a decrease in performance and if left constantly will suffer damage which will ultimately lead to downtime. Problems arising from this downtime include production delays, loss of effective time to produce, thus affecting the productivity of the company. The results show the lowest availability ratio value occurred in September 2017, this is because the total downtime is high during 4610 minutes due to trouble and waiting time during 1920 minutes for recovery. Performance efficiency ratio of the amount of fuel used is high at 35 Kg /cm3due to recovery from the beginning. Rate of quality machine shows good results, this is because no reject is happening.